PENGARUH PEMBERDAYAAN, MOTIVASI DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL (STUDI PADA DINAS PERTANIAN PERKEBUNAN DAN KEHUTANAN KABUPATEN TEMANGGUNG) - 11.52.02.0104, Agung Wibowo (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study examines the question of how the influence of the effect of empowerment, motivation and organizational climate on employee performance with mediation organizational commitment in the Department of Agriculture and Forestry Plantation Temanggung Regency. The purpose of this stydy was to analyze a). Positively influence empowerment on organizational commitment, b). Positive influence motivation on organziational commitment, c). Positively influence organizational climate on organizational commitment, d). Positive influence employee empowerment on performance, e). positively influence employee motivation on performance, f). Positively influence organizational climate on employee performance, g). Influence of organizational commitment on employee performance. The study population was all employee who work at the Department of Agriculture and Forestry Plantation Temanggung Regency totaled 71 persons, using cencus techniques. Number of respondent surveyed was 71. Methods used in data collection questionnaire (questionnaire) given to the respondents. Test on instrument validity study conducted with factor analysis and Cronbach alpha reliability test, statistical test equipment being used is multiple regression analysis, t-test statistics to prove the hypothesis of the proposed research and trials to test the mediating effect of organizational commitment as a variable. Results of data analysis showed that the empowerment and motivation had no effect on organizational commitment, organizationa climate where as significant positive effect on organizational commitment. Empowerment does not affect on performance but employee motivation and organizational climate significant positive effect on employee performance. Organizational commitment not affect on employee performance. The study found no indication that the effect of empowerment, motivation and organizational climate to employee performance is mediated by organizational commitment variables. Keyword : empowerment, motivation, organizational climate, organizational commitment, and employee peformance